Vacancy-solute complexes and their clusters in iron (2006)
ABSTRACT: In this contribution, several vacancy-solute complexes in iron are investigated theoretically from the viewpoint of positron annihilation. In particular, V-Si, V-P, V-Cr, V-Mn, V-Ni, V-Cu and V-Mo complexes are examined. In addition, nano-sized vacancy-Cu clusters in the Fe matrix are also studied. We concentrate on positron lifetimes and coincidence Doppler broadening profiles that bring complementary information about the studied complexes and their clusters. Positron calculations are carried out using the atomic superposition method employing realistic atomic configurations obtained recently using an ab initio pseudopotential method (vacancy-solute complexes) and Monte Carlo/molecular dynamics methods (vacancy-Cu clusters). The main aim of this study is to predict as to what extent such defects are detectable and differentiable using positron annihilation techniques. The results obtained are discussed in the context of experimental data available in the literature.